Accelerating electrochemical repair rate for cracked cement composites: Effect of carbon nanofiber. (20th December 2021) - Zhang, Qian; Yuan, Lianwang; Zhou, Zonghui; Wang, Jinbang
Highlights: Influence of CNF dosage on the electrochemical repair rate is studied. That CNF contributes to deposits enrichment is observed directly. The mechanism of CNF on electrochemical repair is depicted. Abstract: Electrochemical repair is a potential technique for underwater crack occurred in cement based materials, especially in hydraulic or marine engineering. One challenge of electrochemical repair is that high resistivity of cement components leads to long repair time (30–90 days). This work successfully accelerates electrochemical repair rate by introducing carbon nanofiber (CNF). The acceleration effect of CNF on electrochemical repair was mainly evaluated by water permeability and ultrasonic technology. Results illustrate that CNF contributes to form conductive pathway, hence obviously decreases the mortar resistivity. Furthermore, CNF is pulled out after specimen crack, and exposed CNF provides nucleation sites for deposits. Specifically, exposed CNF acts as micro cathode when apply direct voltage, results in the enrichment of Mg 2+ around CNF, and accelerates the generation of deposits.